Los archivos ficcionales de las taperas del “desierto”: en Lincoln, en Quiñihual (Anclajes, 2023)
Starting with the liberal projects of modern nation-state formation, our territory had to be desertified to imagine, build and sustain this process. To challenge these policies and their narratives, it becomes necessary to rewrite new fictions. We begin by examining the figure of the taperas, legacy of the 19th century modernizing project, as a dynamic component of the landscape and, at the same time, as a critical device waiting to be questioned and exhumed as a surviving trace. In this way, the encounter among the poetic traces in the Quiñihual railway station, the vital traces that inhabit the LincoRln desert’s Tapera del desierto and the map that emerges between them, interrupt and destabilize the story imposed in the territory of the province of Buenos Aires.
Keywords: Archives; Art and literature; Desert; State Policies; Territory